Pengaruh Produk Domestik Bruto, Suku Bunga, Kupon, Jatuh Tempo Dan Inflasi Terhadap Yield To Maturity Periode 2018-2022 - Muhammad agung rizki; Elsye Fatmawati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to test whether Gross Domestic Product (GDP), interest rates, coupons, maturity and inflation affect the Yield To Maturity (YTM) of Government Bonds. The data used is the type of government bonds with Fixed Rate (FR) coupons denominated in Rupiah 2018 – 2022. The method used is a purposive sampling method, so that a sample of 23 FR series bonds is obtained. The type of research used is quantitative research, which is to prove the relationship between independent and dependent variables. The results of this study show that partially GDP does not have a positive effect on YTM, interest rates do not have a positive effect on YTM, coupons have a positive effect on YTM, maturity does not have a positive effect on YTM and inflation does not have a negative effect on YTM.